Direct visualization of antigen-specific CD8+ T cells during the primary immune response to Epstein-Barr virus In vivo. - Callan, M; Tan, L; Annels, N; Ogg, G; Wilson, J; O'Callaghan, C; Steven, N; Mcmichael, A; Rickinson, AB (1998)
Primary infection with virus can stimulate a vigorous cytotoxic T cell response. The magnitude of the antigen-specific component versus the bystander component of a primary T cell response remains controversial. In this study, we have used tetrameric major histocompatibility complex-peptide complexes to directly visualize antigen-specific cluster of differentration (CD)8+ T cells during the primary immune response to Epstein-Barr virus (EBV) infection in humans. We show that massive expansion of activated, antigen-specific T cells occurs during the primary response to this virus. In one individual, T cells specific for a single EBV epitope comprised 44% of the total CD8+ T cells within peripheral blood. The majority of the antigen-specific cells had an activated/memory phenotype, with expression of human histocompatibility leukocyte antigen (HLA) DR, CD38, and CD45RO, downregulation of CD62 leukocyte (CD62L), and low levels of expression of CD45RA. After recovery from AIM, the frequency of antigen-specific T cells fell in most donors studied, although populations of antigen-specific cells continued to be easily detectable for at least 3 yr.